Atherogenic lipoprotein profile associated with anthropometric indices of obesity and their association with cardiometabolic risk markers: a cross-sectional study in community. (3rd October 2022) - Wei, D; Melgarejo, J; Vanassche, T; Van Aelst, L; Janssens, S; Verhamme, P; Redon, J; Zhang, Z Y
Abstract: Background: Obesity, especially abdominal fat accumulation, is strongly associated with various metabolic comorbidities. Whether simple anthropometric measures are independently associated with atherogenic lipoproteins is not completely clear. Methods: We randomly recruited 505 participants (51.5% women; mean age: 48.8 years) from the Flemish community, who had undergone lipoprotein particle measurements by nuclear magnetic resonance spectroscopy and conventional lipid measurements. Each lipoprotein fraction was subgrouped into large, medium, and small subclass. Anthropometric measures included body mass index (BMI) and waist-to-hip ratio (WHR), and defined BMI obesity as BMI ≥30 kg/m 2, and WHR obesity as WHR ≥0.85 (women) or 0.9 (men). Results: In the multivariable logistic regression analysis, total very-low-density lipoprotein (VLDL) particle and its subclasses were positively associated with BMI obesity (adjusted odds ratio [OR] for total VLDL: 2.37; 95% confidence interval [CI]: 1.70–3.31) and WHR obesity (OR for total VLDL: 2.06 [95% CI: 1.55–2.73]). The level of total high-density lipoprotein (HDL) particle and its subclass was negatively associated with BMI (OR for total HDL: 0.63 [95% CI: 0.45–0.90), but not with WHR (P≥0.11). None of the low-density lipoprotein (LDL) particles was associated with the two types of obesity (P≥0.092). BMI was inversely associated with the size of LDL and HDL particles, whereas high WHR was significantly associated with smaller VLDL and HDL sizes. For conventional lipid measures, both BMI and WHR were independently associated with high triglyceride and remnant cholesterol, both mainly driven from VLDL particles, and low HDL cholesterol (P≤0.008). These associations were confirmed in multivariable linear regression analysis, except the association of BMI with HDL number and the association of WHR with HDL size. With partial least squares analysis, the lipoprotein profiles of BMI and WHR were significantly associated with a high 10-year cardiovascular disease risk score, the homeostasis model assessment-estimated insulin resistance (HOMA-IR), and C-reactive protein. Conclusion: BMI and WHR were independently associated with high triglyceride-rich lipoproteins, decreased HDL cholesterol. The size of LDL and HDL was more consistently associated with BMI than WHR. The lipoprotein alterations may link obesity with high cardiometabolic risk. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): The European Research Council; the European Research Area Net for Cardiovascular Diseases